Kontrol Morfologi pada Profil Vertikal Endapan Nikel Laterit Pulau Kabaena bagian Selatan, Sulawesi Tenggara - Jana Cindy Salinding; Masri Masri; Hasria Hasria; Ujang Sugiarno (Universitas Halu Oleo, 2025)
The southern part of Kabaena Island in Southeast Sulawesi lies within the East Sulawesi Ophiolite Belt and hosts abundant potential for lateritic nickel deposits; yet morphological controls on the thickness and distribution of nickel grades remain poorly understood. This study analyses how variations in topography influence lateritic nickel deposits, focusing on laterite thickness and nickel grade, using morphometric and morphography data derived from a digital elevation model (DEM) and geochemical data from 78 exploration drill holes. Besides examining cross sections, we assessed the distribution of laterite thickness and nickel grade by slope angle and elevation through linear regression. Lateritic nickel profiles can be classified by slope classes (gentle, moderately steep, steep), each showing distinct profile forms and nickel enrichment zones. The results indicate a positive correlation between elevation and laterite thickness (R = 0.52), whereas nickel grade shows a negative trend, decreasing at higher elevations (R = –0.56). In contrast, slope exhibits weak correlations with both laterite thickness (R = 0.20) and nickel grade (R = 0.14), suggesting slope variation does not significantly influence either parameter relative to elevation. On gentle slopes, average nickel grades are relatively higher than on steep and moderately steep slopes, with laterite thickness varying. The observation that laterite profiles differ at similar elevations and slopes implies that other geological factors also influence the distribution of lateritic nickel.